2009
DOI: 10.1139/o09-062
|View full text |Cite
|
Sign up to set email alerts
|

NuA4 and SWR1-C: two chromatin-modifying complexes with overlapping functions and componentsThis paper is one of a selection of papers published in this Special Issue, entitled 30th Annual International Asilomar Chromatin and Chromosomes Conference, and has undergone the Journal's usual peer review process.

Abstract: Chromatin structure is important for the compaction of eukaryotic genomes, thus chromatin modifications play a fundamental role in regulating many cellular processes. The coordinated activities of various chromatin-remodelling and -modifying complexes are crucial in maintaining distinct chromatin neighbourhoods, which in turn ensure appropriate gene expression, as well as DNA replication, repair, and recombination. SWR1-C is an ATP-dependent histone deposition complex for the histone variant H2A.Z, whereas NuA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 152 publications
0
60
0
1
Order By: Relevance
“…The SET7 H3K4 methyltransferase, implicated in signal-regulated transcription activation (Keating and El-Osta, 2013), exhibits signal-induced recruitment to Egr1 and is therefore likely to act directly. RUVBL2 and KAT5 are both found in the TIP60 acetyltransferase complex (Lu et al., 2009), but recent studies suggest that KMT3C acts predominantly on non-histone substrates (Olsen et al., 2016); further work will be required to elucidate their roles.…”
Section: Discussionmentioning
confidence: 99%
“…The SET7 H3K4 methyltransferase, implicated in signal-regulated transcription activation (Keating and El-Osta, 2013), exhibits signal-induced recruitment to Egr1 and is therefore likely to act directly. RUVBL2 and KAT5 are both found in the TIP60 acetyltransferase complex (Lu et al., 2009), but recent studies suggest that KMT3C acts predominantly on non-histone substrates (Olsen et al., 2016); further work will be required to elucidate their roles.…”
Section: Discussionmentioning
confidence: 99%
“…The NuA4 histone acetyltransferase acts upstream, depositing an acetyl group on the histone H4, resulting in the recruitment of Bdf1p and SWR1-C [15]. Recent work has revealed that mutations in NuA4 subunits, Bdf1p, SWR1-C, or H2AZ render cells hypersensitive to DNA damage agents, suggesting that histone acetylation-mediated H2AZ deposition plays crucial roles in the DNA damage response [16]; [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that NuA4 binds the INO1 promoter (Konarzewska et al 2012). It is also important to note that some of the subunits of the NuA4 complex are shared with the SWR-C complex that is responsible for loading the modified H2A.Z into nucleosomes and H2A.Z is involved in regulation of INO1 (Lu et al 2009). However, none of the SWR-C−specific components were identified in our screen suggesting that the Opi − phenotype is specific to the NuA4 complex.…”
Section: Resultsmentioning
confidence: 99%